Pendampingan Penggunaan Software Bank Mini Online Sebagai Media Pembelajaran Bagi Siswa/i SMK Yapisa Terpadu Megamendung Bogor - Muanas, Muanas; Mulia, Isnan; Marlina, Tri; Herawati, Heti (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
The objectives of the activities carried out are: 1). To introduce online mini bank software to students of Yapisa Integrated Vocational School, Megamendung, Bogor City. 2). Providing an understanding of the use of online mini bank software to students of Yapisa Terpadu Megamendung Bogor City. 3) To find out the obstacles experienced when operating the online mini bank software by students of Yapisa Terpadu Megamendung Vocational School, Bogor City. Yapisa Terpadu Megamendung Vocational School, Bogor City has implemented basic banking subjects and Accounting Practicum for Service, Trade and Manufacturing Companies. However, up to now, the process of practicing basic banking subjects and Accounting Practicum for Service, Trade and Manufacturing Companies is still done manually. Therefore, it is important to introduce and increase students' knowledge that in practice online mini bank software is available to support technological advances in the world of education. The methods used in mentoring are: Lecture, Question and Answer and Simulation. The outcomes that are expected to be realized from this activity are: (1) Increasing students' understanding regarding the use of online mini bank software. (2) Improving skills in operating online mini bank software for students of Megamendung Integrated Vocational School Yapisa. Keywords: online mini bank software, vocational school, students